Corrigendum to ‘ Fine tuning of the magnetic properties in Mn3−xCoxGa Heusler films near the critical regime’ [J. Alloy. Compd. 858 (2020) 158288] (Journal of Alloys and Compounds (2021) 858, (S092583882034651X), (10.1016/j.jallcom.2020.158288)) - Lee, Kyujoon; Yoo, Woosuk; Nguyen, Quynh Anh T.; Bang, Hyun-Woo; Kim, Hyeonsu; Klaeui, Mathias; Rhim, Sonny H.; Jung, Myung-Hwa (Journal of Alloys and Compounds, 2021)
The authors regret that the printed version of the above article contained a number of errors. The correct and final version follows. The authors would like to apologise for any inconvenience caused. In conclusion (page 6 Line 4–6), “First-principles calculations reveal that the Co substitution prefers Mn-II site substitution, which coupled antiferromagnetically …”. The correct statement should be “First-principles calculations reveal that the Co substitution prefers Mn-II site substitution, which coupled ferromagnetically …”.
CRIS-Team Scopus Importer:2023-03-27